Zeolites to unlock phosphorus fixation in agriculture - Haruna, Ahmed Osumanu; Hasbullah, Nur Aainaa; Ab. Majid, Nik Muhamad (Universiti Putra Malaysia Press, 2017)
This book is based on the writers experiences in soil science, fertilizer, and zeolite research at UPM. It is intended to provide the general public, academicians, research scientists, agriculturists, students, environmentalist, and others with information on using clinoptilolite zeolite to optimize the use of inorganic fertilizers in cultivating acid soils. We are motivated to write this book because to the best of our knowledge, there is a dearth of information in the field of agricultural and environmental sciences that provide specific information on sustainable management of inorganic fertilizers in tropical acid soil using zeolite.